(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Architectural education has never been limited to the transmission of technical drafting skills or the memorization of stylistic precedents; at its core, it is an intellectual, artistic, cultural, and ethical formation through which a student learns to transform space into meaningful human environment. Within this formation, the discipline of architectural composition and fundamentals of design occupies a foundational place because it mediates between perception and construction, idea and form, intuition and method, aesthetic intention and functional necessity. This article examines the role and significance of architectural composition and fundamentals of design in architectural education through an integrated theoretical and pedagogical lens. The study argues that this discipline is not a supplementary artistic component added to professional preparation, but rather the generative framework through which future architects acquire spatial literacy, compositional thinking, proportioning skills, conceptual clarity, and the ability to organize visual, structural, and social relationships into coherent architectural propositions. Drawing on classical architectural theory, modern design pedagogy, environmental psychology, and contemporary educational approaches, the article analyzes how compositional training shapes students’ perception of form, order, rhythm, scale, context, and tectonic articulation, while also supporting problem-solving, critical reflection, and interdisciplinary thinking. The results show that the educational value of the subject lies in its ability to establish the grammar of architectural expression, to cultivate professional judgment at the early stages of formation, and to prepare students for more advanced design studios, technical disciplines, and real-world project work. The discussion further demonstrates that when architectural composition is taught as a living method of inquiry rather than a rigid catalog of formal rules, it becomes a strategic instrument for balancing artistic originality, environmental responsibility, cultural identity, and technological change. The article concludes that the status of this discipline in architecture curricula must be understood as fundamental, formative, and system-defining, because without it architectural education risks producing competent draftsmen without spatial imagination, or expressive form-makers without architectural discipline.